Gerakan Politik Kiai dan Dakwah Islam: Membaca Aktifitas Dakwah dan Politik Kiai pada Momentum Pemilu - Rosi, Fathor (At-Turost : Journal of Islamic Studies, 2020)
When the momentum of the general election (Pemilu), the participation of the Kiai became a lot of spotlight and opposition because it was often considered political, and vice versa even though political activity was often a media of preaching. So the purpose of the discussion in this article is to read the preaching and political activities of the Kiai during the election momentum. This study uses literature review with empirical and theoretical analysis, including journals, books, and other communication media. The results of this article intend to emphasize that the preaching of the Kiai and politics can be combined by making politics as wasilah convey the message of Islamic da'wah. Because operationally it is recommended to use various methods and media, including power, but what needs to be underlined that power is not the purpose of da'wah. In the context of preaching, Kiai is closely related to politics. When the rulers of a country or region are hostile to Islam, the policies made can interfere with Islamic preaching activities. So, the relationship of politics or power with preaching will help achieve the goals of da'wah. So that the purpose of da'wah can run well if it is supported by a strong organization or by policy makers. At least between the Kiai as a religious figure who consistently carries out his preaching activities, fully supported by the ruling government, a synergy will be created between the Kiai as an ulama 'and the Government as an umara'.